Mineral Resource Taxation in Poland as Environmental Revenue - Ochot, Artur (Journal of Finance and Financial Law, 2022)
The purpose of the article/hypothesis. The statistics on environmental taxes in Poland lack a very specific resource taxation in form of the tax on extraction of certain minerals and the exploitation levy, which is the subject of this article. This paper aims to provide a proof that these taxes should be considered environmental in nature and as such are required to be reported by the European law. Thus, the article suggests and recommends that national environmental tax revenues data should be corrected.Methodology. First, the law and literatue overview is presented, taking view on the characteristics of environmental taxes and placing those taxes that are subject of this article into this category. Next, fiscal importance of those taxes is measured within budgets of its receivers. Additionally, the article provides the information on how much environmental tax statistics would have changed after taking into consideration the taxes discussed in this article. The research period of this study is 2012–2020. It is dictated by the introduction of tax on certain mineral extraction and the latest budget reports available. The research is limited by the accessibility of public data which does not provide separate accounts of hydrocarbon taxes (which should be excluded from environmental data) and taxes on other minerals.Results of the research. The overview of the literature provides some evidence that the exploitation levy should be treated as a tax and, together with the tax on certain mineral extraction, should be treated as environmental in nature. Thus, they should be implemented in national environmental tax statistics. Although majority of environmental tax revenues is made by taxes on energy, the result of this implementation would significantly change values of taxes on pollution and resources, making it second (out of three) most important category within environmental taxes in Poland.